Fundamentals of credit and credit analysis - Ziegel, Arnold (Stowe, Vermont : Mountail Mentors Associates, 2014)
This book is conceived and written as a result of the development of these courses and experience on corporate banks. It illustrated the issues of credit and credit analysis in a manner that tries to take away its mystery.
Chapter1. Introduction- the goals and nature of credit analysis -- Chapter2. Capital structure and debt capacity -- Chapter3. Fundamentals of Financial Analysis -- Chapter4. Credit risks, cash flow and capital structure -- Chapter5. Principles of extending credit -- Chapter6. Cash flow analysis and forecasting -- Chapter7. The process of credit analysis- making credit decision -- Chapter8. Use of credit structure to modify risk commercial finance and structured finance .
Keywords: CREDIT AND ANALYSIS